Implementasi Peraturan Bupati Nomor 05 Tahun 2018 tentang Pedoman Pengelolaan Alokasi Dana Desa dalam Perspektif Hukum Islam (Studi Di Desa Lapoa Indah Kecamatan Andoolo Kabupaten Konawe Selatan) - Siti Nurhidayah; Sitti Halimang; Muh. Asrianto Zainal (QAIMUDDIN: Journal of Constitutional Law Review, 2021)
This research began with local community complaints that community empowerment did not work effectively and efficiently. The most effective and faster direction for village community empowerment to achieve goals is to involve the community. However, in practice, the allocation of village funds is mostly used for infrastructure development and rarely pays attention to the community empowerment process. There are 3 problem formulations in this study, namely, first how is the form of community empowerment in managing village fund allocations, secondly how is the impact of community empowerment in managing village fund allocations in Lapoa Indah village, third how is the perspective of Islamic law on community empowerment in managing village fund allocations. The purpose of the study was to answer the formulation of the problem in this study.This type of research is qualitative, namely research on descriptive research and tends to use analysis, with an empirical normative approach with primary and secondary data sources. This study uses data collection techniques, observation, interviews, and documentation. The data analysis is an activity in research in the form of conducting a study or review of the results of data management assisted by the theories obtained previously.The results of this study illustrate that the ongoing form of community empowerment is empowering farmer groups in the form of providing nutmeg and coffee seeds, providing fertilizer and agricultural tools, namely tractors or dompeng, empowering PKK women in the form of renting catering equipment, and empowering al-qur' education parks. an for children. Meanwhile, the resulting impacts are positive and negative impacts. The positive impact of good community participation is the granting of land for the construction of farm roads, increasing agricultural yields. While the negative impacts are the lack of openness or transparency of the government and the lack of potential human resources. There are Islamic legal perspectives that are appropriate and some are not, which is in accordance with the empowerment of PKK mothers, and the empowerment of the Qur'an education park. Meanwhile, what is not appropriate is due to the lack of transparency of the village government and the lack of potential human resources.